Sustainable Blocks Reinforced with Agave americana L. Fiber and Its Mechanical Properties - Valenzuela Inga, Albert Jorddy (2023)
The study of sustainable construction materials is getting attention, since the materials must be ecological, recyclable and renewable to generate a positive impact on the environment as a substitute for the construction materials currently used in rural areas of Huancayo. The objective of this research is to determine a sustainable material with resistant mechanical properties, such as reinforced blocks with Agave americana L fiber. The block components were sand, clay and silt, in order to evaluate its behavior, 5 dosages of fiber were proposed: 0%, 0.25%, 0.5%, 0.75% and 1%, these were expressed with respect to the total weight of the sample, on the other hand, the fiber used was cut to obtain a length of 25mm. Strengths were evaluated using the simple compression method, the Brazilian diametral compression tensile method and the modulus of rupture method. The result for the most optimum compressive strength was given when using the dosage of 0.25% of agave fiber increasing by 13.39% (2.54MPa), while, the tensile strength increased by 39.13% (0.32MPa) using 1% of agave fiber, finally an increase of 14.29% (1.44MPa) was obtained in the flexural strength with 0.5% of Agave americana L. fiber. It concludes that the use of Agave americana L. fiber improved the mechanical strength of blocks, setting an optimum addition of 0.25% of fiber.